A friction circle concept for Dugoff's tyre friction model. (5th August 2014) - Guntur, R.; Sankar, S.
This paper presents a method of simplifying the calculations required when Dugoff's tyre friction model is used for simulation purposes. It also provides a physical interpretation in that it brings to light an idea similar to the traditional friction circle concept implicit in Dugoff's model. The procedure for calculating the tyre forces is presented, together with a flow chart for use in preparing a suitable computer model.